Cote d'Ivoire : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
The economy proved resilient to Covid-19 and continued recovering in 2021, with growth estimated at 7 percent. Growth is forecasted to slow to 6 percent this year due to the war in Ukraine. Inflation increased to 4.2 percent last year, on the back of surging food prices, and is expected at 5.5 percent this year, while the current account deficit is projected to reach 4.8 percent of GDP. Risks are tilted to the downside, as a result of the war in Ukraine, global financing conditions, and regional instability.